2014
DOI: 10.1007/s10072-014-1961-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polymorphic metabolism enzymes on serum phenytoin level

Abstract: Phenytoin has a widespread use in epilepsy treatment and is mainly metabolized by hepatic cytochrome P450 enzymes (CYP). We have investigated CYP2C9*2, CYP2C9*3, CYP2C19*2 and CYP2C19*3 allelic variants in a Turkish population of patients on phenytoin therapy. Patients on phenytoin therapy (n = 102) for the prevention of epileptic seizures were included. Polymorphic alleles were analyzed by restriction fragment length polymorphism method. Serum concentrations of phenytoin were measured by fluorescence polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Similarly the mean serum concentration of phenytoin of the polymorphic patients with epilepsy was higher than that for the wild-type alleles both in the monotherapy and polytherapy patients in a study done by Ozkaynakci A et al [ 24 ].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly the mean serum concentration of phenytoin of the polymorphic patients with epilepsy was higher than that for the wild-type alleles both in the monotherapy and polytherapy patients in a study done by Ozkaynakci A et al [ 24 ].…”
Section: Discussionmentioning
confidence: 97%
“…The cytochrome P450 isoenzyme CYP2C9 plays an important role in the metabolism of many therapeutically important drugs such as phenytoin [14], S-warfarin [15], tolbutamide [16], losartan [17], and non-steroidal anti-inflammatory agents (NSAIDs) [13] in vitro and/or in vivo. Inter-individual differences in CYP2C9 metabolic activity have been linked to dosing difficulty that might lead to ineffective treatments or worse, toxicity [18].…”
Section: The Pharmacogenetics Of Cyp2c9mentioning
confidence: 99%
“…Both variants exhibit reduced functional activity, with losses of 29 and 94% enzymatic activity reported for CYP2C9*2 and *3 , respectively, when compared with the wild-type genotype [ 125 , 126 ]. Three of the included studies investigated CYP2C9 genotypes [ 42 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ozkaynakci et al [ 44 ] reported data for 11 different combinations of CYP2C9 and CYP2C19 genotypes; therefore, the independent impact of the CYP2C9 genotype on serum phenytoin concentrations was difficult to discern. When compared with the CYP2C9 and CYP2C19 wild-type genotype group, CYP2C9*1/*3 , CYP2C19*2/*3 was the only genotype group with a serum phenytoin trough that was significantly different, with a mean concentration that was 20.47 mg/L higher than the wild-type genotype group ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%